Determinants of employee retention at IME Group of Companies / Amiradilah Suparman - Suparman, Amiradilah (Faculty of Business and Management, 2015)
The employee retention is a continuous problem or issues that always be a major issue of any company. This is not easy to retain employee for a long period in an organization. This research has been conducted to know and investigate the determinants of employee retention at IME Group of Companies. It is important to the company to reduce the employee turnover that may influence the productivity of company. The data collected through the questionnaires from 80 respondents but however only 60 respondents reply. The questionnaires were distributed to test the hypotheses that are proposed. The questionnaires designed based on three variables that are expected to be factors that influence employee retention which are working environment, supervisor support and monetary rewards. The results from this study reveal that there is positive relationship between all independent variables which are working environment, supervisor support and monetary rewards towards employee retention. There are many other factors that may influence employee retention which are not included in this research. The sample of this study only limited to the employees that are working at IME Group of Companies in Petaling Jaya branch only.